The Influence of Bibliocounseling to Enhance Student’s Academic Self-Regulation - Ikhsan, Ikhsan; Saman, Abdul; Hadi, Purwaka (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2019)
The purposes of this research are to discover (1) the description of academic self-regulation before and after bibliocounseling treatment to students, (2) the implementation of bibliocounseling to increase academic self-regulation of students, (3) the influence of bibliocounseling to academic self-regulation of students. The approach used in this research is quantitative approach by using quasi-experimental design with non-equivalent control group design. The subjects of this research were 30 students of class VIII who, identified as having low learning self-regulation and they were divided into two groups, namely experimental group, and control group. Techniques for collecting the data employ self-regulation learning scale, observation, and interview. The results of this research reveal that (1) the level of academic self-regulation of a student in SMPN 1 Makassar is low before giving bibliocounseling. However, after implementing it in 4 sessions, the level of academic self-regulation of students improve to hight category, (2) the result of statistic descriptive analysis obtains that essentially there is a change of the level of academic self-regulation of students after giving bibliocounseling and the result of hypothesis test shows that there is positive influence on the implementation of bibliocounseling to increase academic self-regulation of the students in SMPN 1 Makassar.